Pelatihan Pengolahan Sampah Menggunakan Maggot untuk Mengurangi Timbulan Sampah Rumah Tangga di Desa Mandiro, Kabupaten Bondowoso - Kirana; Nurhalisa, Siti; Alfaidah, Catryna; Amalia, Shofiya; Imamah, Dina Yusrotul; Fakhiroh, Lailah Izza; Steven, Syahrul; Akbar, Syarifil Hidayatul; Rokhmah, Dewi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Waste is a global problem in various countries, including Indonesia. Based on SIPSN data (2023), Indonesia has a total waste generation of 34,599,396.49 tons/year, with 51.11% of waste coming from household activities. Mandiro is one of the villages in Bondowoso Regency that still has problems with household waste management. Waste is simply dumped in vacant lots and water bodies that are not supposed to be used as landfills. This triggers environmental pollution that can also have an impact on health. The purpose of this training and mentoring activity is to improve the skills and knowledge of ELANGGHU Environmental Cadres related to waste management with maggots so that ELANGGHU Environmental Cadres can actively participate in reducing household waste in Mandiro Village. In this activity, two methods were used, namely education through providing materials and direct demonstrations to further improve the understanding of ELANGGHU Environmental Cadres. From the results of the pre-test and post-test, it can be seen that there is an increase in the knowledge of ELANGGHU Environmental Cadres regarding waste processing using maggots by up to 100%.